Optimization of sustainability and resilience for transportation projects - Kumar, Shantanu, author; Mehany, Mohammed Hashem, advisor; Grigg, Neil, committee member; Abdallah, Moatassem, committee member; Atadero, Rebecca, committee member; Fisher, Gwen, committee member (Colorado State University. Libraries, 2023)
The state of America's infrastructure is old and has been deteriorating and is in need for severe rehabilitation and maintenance. The population has been increasing which has increased the demand for new transportation projects over the last decade. Therefore, it is essential to not just construct new transportation projects but invest in the rehabilitation and maintenance of the existing infrastructure. The transportation sector has the highest greenhouse gas (GHG) emissions among all infrastructure projects. In the transportation sector, the roads and highways subsector have the highest associated emissions which calls for projects in this subsector to be more sustainable. Concurrently, it has been observed that the frequency of natural disasters has increased exponentially in the last few decades which has increased the need to be more resilient. Sustainability and resilience are intertwined but different concepts that need to be explored and analyzed together. Both sustainability and resilience have been quantified using a variety of different methods, and rating system have been one of the most common and widely used methods across the globe for infrastructure projects. In North America (especially the US), the ENVISION rating system created through join efforts of the Harvard graduate School of Design's Zofnass Program of Sustainable Infrastructure and the Institute of Sustainable Infrastructure, has been the most widely used rating system for various infrastructure projects, especially transportation projects. Often, achieving sustainability and resilience is associated with a higher cost. This research proposed optimizing sustainability and resilience while minimizing the life cycle cost (LCC) and GHG emissions using the NSGA-II algorithm. It takes input of all possible strategies within the different dimensions of sustainability and resilience and uses the abovementioned algorithm to determine a list of pareto optimal solutions. These solutions represent a space of acceptable solutions which have high sustainability and resilience while also having low GHG emissions and LCC. This model is intended to assist stakeholder in making decisions to improve the sustainability and resilience while promoting a life cycle thinking. It also provides a unique database creation idea for keeping all sustainable and resilient strategies for different infrastructure projects in one place which can promote an open access feature as more transportation agencies and stakeholders buy-in to the idea of using this model.
Keywords: NSGA-II; rating systems; sustainability; optimization; decision-making; resilience